2018
DOI: 10.7567/apex.11.033004
|View full text |Cite
|
Sign up to set email alerts
|

Charge-state control of ensemble of nitrogen vacancy centers by n–i–n diamond junctions

Abstract: We fabricated n-type–intrinsic–n-type (n–i–n) diamond junctions to stabilize negatively charged nitrogen vacancy (NV−) centers. An ensemble of NV centers was generated in a high-purity intrinsic diamond in order to maintain the spin coherence time. The Fermi-energy of the i-layers was controlled by band bending at the two n–i junctions. We confirmed that the NV centers can be modulated toward NV− centers by decreasing the width of the i-layers between adjacent n-layers. The spin coherence time for the NV− cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…1B, inset) (32). The location in depth of the observed defects is consistent with isolation to the i-type layer, as expected from formation energy calculations (35) and the local Fermi level (36). This depth localization provides an alternative to delta-doping (37), which is not possible with intrinsic defects, facilitating positioning and control in fabricated devices ( Fig.…”
Section: Isolated Single Defects In a Semiconductor Devicesupporting
confidence: 82%
See 1 more Smart Citation
“…1B, inset) (32). The location in depth of the observed defects is consistent with isolation to the i-type layer, as expected from formation energy calculations (35) and the local Fermi level (36). This depth localization provides an alternative to delta-doping (37), which is not possible with intrinsic defects, facilitating positioning and control in fabricated devices ( Fig.…”
Section: Isolated Single Defects In a Semiconductor Devicesupporting
confidence: 82%
“…The location in depth of the observed defects is consistent with isolation to the i-type layer. This is to be expected because formation energy calculations (35) indicate that the neutral charge state is energetically favorable when the Fermi level is between ~1.1 and 2 eV, and this condition must be satisfied somewhere in the i-type layer (32,36). This depth localization provides an alternative to delta doping (37), which is not possible with intrinsic defects, facilitating positioning and control in fabricated devices (fig.…”
Section: Isolated Single Defects In a Semiconductor Devicementioning
confidence: 97%
“…They can therefore be used as a footprint for the centre's environment and we propose to use this technique for the quality control of optical centres. Much effort was made to stabilise [85,86] and/or tune and control the charge state of colour centres, especially with the NV centre: chemically [94][95][96][97], optically [98], and electrically [17,18,99,100]. It was shown by a single-shot chargestate readout that the NV centre charge state is constantly 'jumping' between NV − and NV 0 under light excitation due to photo-induced ionisation and recharging [101].…”
Section: Charge State and Fluorescence Stability-time Trace Analysismentioning
confidence: 99%
“…In spite of the detrimental impact of charge state instability on spin polarization [13,17], and consequently on the sensing capabilities of NV centers, a clear understanding of charge dynamics of NV ensembles is lacking. * rakshyakar.giri@iit.it Attempts to control the charge states of NVs by manipulating the Fermi level are reported in the literature [11,[18][19][20][21][22]. It was demonstrated that an ensemble of NV centers could be stable enough to be used as a charge based data storage medium [23,24].…”
Section: Introductionmentioning
confidence: 99%